Assessment of Knowledge, Attitude and Practice Regarding Management of Hypertension among Saudi Population (Journal of Food and Dietetics Research, 2025)
Background: Hypertension, defined as a blood pressure of ≥130/80 mmHg in adults by the American Heart Association,  remains a leading cause of global morbidity and mortality. It contributes significantly to coronary artery disease and  cerebrovascular events. The global prevalence is estimated at 26% (972 million people) and is expected to rise to 29%  by 2025, especially in developing countries. This study aimed to assess the knowledge, attitudes, and practices (KAP)  related to hypertension management among the Saudi population in Hail City. Materials and Methods: A retrospective  cross-sectional study was conducted using a structured questionnaire comprising three sections: knowledge (scored  based on correct responses), attitude (assessed using a Likert scale), and practices (based on frequency of behaviors).  Results: More than 80% of subjects expressed concern about long-term medication use, engaged in regular exercise, and  preferred home-cooked meals with fruits and vegetables. About half of the hypertensive subjects reported daily blood  pressure monitoring and adding lemon to salads. The study revealed an overall acceptable level of KAP. Significant  fair positive correlations were found between KAP and age, income, and education level (p < 0.05). Conclusion: Most  respondent’s demonstrated good knowledge and positive attitudes toward hypertension management, with KAP signifi cantly associated with demographic factors.
Keywords: Hypertension; Knowledge; Attitudes; Practice; Health Behavior; Cross-Sectional Studies; Saudi Arabia